KORELASI PERAN HAKAM (JURU DAMAI) DENGAN MEDIATOR DALAM PROSES MEDIASI PERKARA PERCERAIAN DI PENGADILAN AGAMA - Suwardi Suwardi (Ensiklopedia Social Review, 2020)
Mediation that is carried out by the mediator in a juridical manner must be carried out before the main examination of the case, and if it is not implemented it will result in the decision being null and void (Supreme Court Regulation Number 1 of 2008). Meanwhile, the legal process that originates from each family party, juridically it is an initiative of the panel of judges to implement (Law on Religious Courts), because in the existing regulations it is stated with the phrase "can", which is based on an interim decision by the panel of judges. those who examine, in fact, in practice, the role of Hakam in divorce proceedings in religious courts is no longer relevant and implemented, because his function has been replaced by a mediator as required by a Supreme Court Regulation, and the litigants tend to be determined to separate.